2007
DOI: 10.1177/1098611106289405
|View full text |Cite
|
Sign up to set email alerts
|

Public-Safety Concerns Among Law Enforcement Agencies in Suburban and Rural America

Abstract: Contingency theory argues that the performance of an organization is contingent on how well it fits the context within which it is embedded. This study explores the public-safety concerns of nearly 6,000 law enforcement agencies serving populations less than 50,000. Property offenses, domestic violence, and drugs were the most frequently reported concerns, whereas gangs and violent crimes were often ranked lower. Rankings of public-safety concerns varied across agencies and were affected by population density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 21 publications
2
44
0
Order By: Relevance
“…Results of this analysis reinforce the observation by Kuhns et al (2007) that the contextual position of an agency shapes its concerns over public and community safety matters (see also Crank & Wells, 1991). Though only modest differences emerged in the homeland security preparation, concerns, and perceptions of small Illinois agencies, where those differences were evident, suggests that an agency's proximity to peers 9 might hold beneficial outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…Results of this analysis reinforce the observation by Kuhns et al (2007) that the contextual position of an agency shapes its concerns over public and community safety matters (see also Crank & Wells, 1991). Though only modest differences emerged in the homeland security preparation, concerns, and perceptions of small Illinois agencies, where those differences were evident, suggests that an agency's proximity to peers 9 might hold beneficial outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…However, officers in small departments tend to deal with a greater variety of crime types and a wider array of issues and are more likely to be generalists than to specialize (Liederbach and Frank, 2003). In addition, public safety concerns vary, with smaller departments having less concern for violence and gang activity; for example, Kuhns, Maguire, and Cox, 2007, shows that concerns regarding alcohol offenses, disorderly conduct, vandalism, traffic offenses, wildlife and agricultural crime, and domestic violence are inversely related to agency size. Despite these generalities, there is considerable variation across small-town and rural agencies.…”
Section: Small and Rural Agencies Law Enforcementmentioning
confidence: 99%
“…Small and rural agencies might also deal with different kinds of incidents from those that large urban agencies handle. One study showed that rates of alcohol offenses, disorderly conduct, vandalism, traffic offenses, wildlife and agricultural crime, and domestic violence were inversely related to agency size (Kuhns, Maguire, and Cox, 2007).…”
Section: Law Enforcement Technology Needs Among Srtb Agenciesmentioning
confidence: 99%
“…A recurring problem cited in the literature on rural policing is that the experiences of urban police are assumed to be universal and thus able to be simply mapped onto the experiences of rural law enforcement (Barrett et al, 2009;Kuhns et al, 2007). For instance, researchers interested in community policing strategies have often assumed rural agencies experience the same distrust and suspicion from citizens as do their urban counterparts, despite the substantial body of evidence that the relationship between rural police and their constituents is significantly different (Weisheit, Falcone, & Wells, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Rural law enforcement devote more time to crime prevention activities, due to the lower number of calls and increased amount of "unassigned free time in each shift to spend on conducting building checks and patrolling hot spots" (Rhodes & Johnson, 2008, p. 192), and spend significantly less time on non-crime service activities, such as investigating noise complaints or dealing with unruly individuals in public spaces, and other such incidents much more common in urban areas (Liederbach & Frank, 2003). Furthermore, the types of crimes rural police are responding to have been changing dramatically over the past 20-30 years, as this period has seen an increase in the reports of gang activity and violent crime in rural areas (Kuhns et al, 2007), as well as the production and distribution of more debilitating and harmful drugs moving into rural areas, with a sharp rise in methamphetamine, heroin, and cocaine usage (Brock, Copeland, Scott, & Ethridge, 2001;Linnemann & Kurtz, 2014).…”
Section: Introductionmentioning
confidence: 99%